Multi‐objective design optimization of microreactor arrays for distributed renewable energy conversion: A case study - Fu, Kaihao; Wang, Xinjie; Li, Ping; Cao, Chenxi; Du, Wenli (AIChE journal, 2023)
Renewable energy accommodation entails extensive use of modular devices, whose performance degrades remarkably from the lab scale to the industrial scale. This work presents a multi‐objective design optimization approach for modular devices scale‐up as exemplified by hierarchical numbering‐up of reverse water‐gas shift microreactors. The optimization objectives cover a wide span of competing system performance metrics, including the reaction performance, energy efficiency, space occupation, environmental impact, and costs. The decision variables involve the hierarchical geometry, branching, and inter‐stack connection schemes of the microreactor stacks. The obtained Pareto‐optimal designs suggest that multiple short stacks with small intra‐stack distribution channels and large inter‐stack connection tubes can well balance cost and performance. Meanwhile, single‐stack structures with large distribution channels are more suitable for portable applications. The methodology not only can be extended to the numbering‐up of various types of microreactors but also has essential guidance for the integration design of other modular devices.